Advanced Performance of Annealed Ni–P/(Etched Si) Negative Electrodes for Lithium–Ion Batteries. Issue 13 (1st January 2017) - Domi, Yasuhiro; Usui, Hiroyuki; Narita, Masakuni; Fujita, Yoshihiro; Yamaguchi, Kazuki; Sakaguchi, Hiroki
Abstract : The electrochemical performance of variously treated Ni–P–coated Si (Ni–P/Si) negative electrodes for lithium-ion batteries was investigated. X–ray diffraction analysis revealed the formation of nickel silicide (NiSi and NiSi2 ) after annealing, which improved the adhesion between the Ni–P coating layer and Si particles. Spotty Ni–P particles did not aggregate on an etched Si surface due to an anchor effect, even after annealing, whereas the particles aggregated on an untreated Si surface. An annealed Ni–P/(etched Si) negative electrode maintained a discharge capacity of 2000 mA h g −1 even at the 100th cycle in an organic electrolyte, which can be attributed to Ni–P particles remaining on the surface of the annealed Ni–P/(etched Si) electrode even after the charge–discharge test. The annealed Ni–P/(etched Si) electrode also exhibited superior cycle performance with a reversible capacity of 1000 mA h g −1 over 750 and 1100 cycles in an organic electrolyte containing film–forming additive and an ionic liquid electrolyte, respectively. Consequently, the annealed Ni–P/(etched Si) electrode achieved both high reversible capacity and long cycle life.